Characterization of Rose Essential Oils by Double-Region Atmospheric Pressure Chemical Ionization Mass Spectrometry (DRAPCI-MS) with Principal Component Analysis (PCA), Hierarchical Cluster Analysis (HCA), and Heatmap Analysis. (13th October 2022) - Li, Minglei; Zhang, Yihan; Xi, Hui; Fu, Yingjie; Wang, Hui; Zhang, Yipeng; Sun, Shihao
Abstract: Double-region atmospheric pressure chemical ionization – tandem mass spectrometry (DRAPCI-MS/MS) was used for the direct determination of the volatiles of Chinese Kushui rose essential oil (CKREO), Bulgaria Damask rose essential oil (BDREO), Turkish Damask rose essential oil (TDREO), and Moroccan Damask rose essential oil (MDREO). Eight shared aroma compounds of rose essential oils (REOs) were identified by DRAPCI-MS/MS. Twenty REOs of different species and geographical origins were conducted by principal component analysis (PCA), hierarchical cluster analysis (HCA), and heatmap analysis. Moreover, the volatile components of REOs were determined by gas chromatography – mass spectrometry (GC-MS). Cluster analysis and a Venn diagram demonstrated significant differences among four populations of REOs. Both methods showed that the REOs from these populations were divided into two groups based on the species, presenting the reliability of the quantitative and chemometrics results of DRAPCI-MS. These results demonstrate that the DRAPCI-MS is suitable to identify the species responsible for the REOs.